Inclusive Education as an Instrument of Social Harmony and Ecological Awareness - Qomariyah, Nurul (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
This study is motivated by the need for an Islamic education model capable of responding to the challenges of a plural society and the increasingly urgent ecological crisis. Inclusive education is considered relevant as it emphasizes the values of rahmah (compassion), tolerance, justice, and responsibility toward the environment. The purpose of this research is to examine how Islamic education implemented at SIT Al Uswah Inclusive School Pamekasan serves as an instrument in fostering social harmony while also cultivating ecological awareness. This study employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings reveal that SIT Al Uswah has successfully integrated Islamic values into inclusive educational practices, as reflected in the social interactions of students with special needs and the habituation of environmentally friendly living through programs such as waste banks, tree planting, waste management, and used cooking oil collection for recycling. Furthermore, the innovation of the Al Uswah Kids Unit provides tangible evidence of inclusivity for students with special needs. The study concludes that inclusive Islamic education at SIT Al Uswah is effective in fostering collective awareness of peaceful coexistence and environmental preservation as a form of social worship. The contribution of this research lies in developing an inclusive Islamic education model integrated with ecological values, which can serve as a reference for building a more humanistic and sustainable society.